2012
DOI: 10.1007/s00125-012-2693-z
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 promotes beta cell regeneration in human and mouse pancreas

Abstract: Aims/hypothesis Diabetes is characterised by loss and dysfunction of the beta cell. A major goal of diabetes therapy is to promote the formation of new beta cells. Polymorphisms of T cell factor 7-like 2 (TCF7L2) are associated with type 2 diabetes, negatively regulating beta cell survival and function. Here, we provide evidence for a role of TCF7L2 in beta cell proliferation and regeneration. Methods Pancreatic sections from three mouse models (high-fat diet, exendin-4 and streptozotocin-treated mice) and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
5
33
0
Order By: Relevance
“…More recently, TCF7L2 expression in the endocrine pancreas was correlated not only with beta cell proliferation, but also with beta cell regeneration in different murine models of diabetes (35). In the same study, it was shown that in human exocrine pancreatic tissue, TCF7L2 overexpression induced beta cell phenotype and insulin production in ductal epithelial cells (35).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More recently, TCF7L2 expression in the endocrine pancreas was correlated not only with beta cell proliferation, but also with beta cell regeneration in different murine models of diabetes (35). In the same study, it was shown that in human exocrine pancreatic tissue, TCF7L2 overexpression induced beta cell phenotype and insulin production in ductal epithelial cells (35).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, it has been shown to be involved in the expression of glucagon-like peptide 1, and gastric inhibitory peptide receptors in beta cells, which mediate the effects of the correspondent incretin hormones to promote beta cell proliferation, neogenesis, and survival in rodent models (34). More recently, TCF7L2 expression in the endocrine pancreas was correlated not only with beta cell proliferation, but also with beta cell regeneration in different murine models of diabetes (35). In the same study, it was shown that in human exocrine pancreatic tissue, TCF7L2 overexpression induced beta cell phenotype and insulin production in ductal epithelial cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…The TCF7L2 gene spans 215.9 kb on chromosome 10q25.3, and its product is a high-mobility box-containing transcription factor involved in the Wnt signaling pathway (10). Wnt pathway activity plays an important role for lipid and glucose metabolism, pancreatic islets proliferation, regeneration and function, and for production of the insulinotropic hormone glucagon-like peptide 1 (GLP-1) (11)(12)(13). Therefore, alteration in this pathway could cause the reduction of GLP-1 secretion, then affecting insulin secretion, and subsequently, among other effects, impairing blood glucose homeostasis.…”
Section: Tcf7l2 Polymorphisms and Type 2 Diabetes Riskmentioning
confidence: 99%
“…Following pivotal studies indicating that the transcription factor 7-like 2 (TCF7L2) is an important risk gene for the development of type 2 diabetes (T2D) (1), great efforts have been made to explore its role as a Wnt signaling molecule in pancreatic b-cells and other tissues including liver (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Although several investigations suggested that TCF7L2 negatively regulates hepatic gluconeogenesis (8,10,11,17), one recent study (7) reported that liver-specific knockout of TCF7L2 reduced hepatic glucose production (HGP), while hepatic overexpression of TCF7L2 increased HGP.…”
mentioning
confidence: 99%
“…Although several investigations suggested that TCF7L2 negatively regulates hepatic gluconeogenesis (8,10,11,17), one recent study (7) reported that liver-specific knockout of TCF7L2 reduced hepatic glucose production (HGP), while hepatic overexpression of TCF7L2 increased HGP. As a result, the controversial issues surrounding the metabolic function of TCF7L2 have been extended from pancreatic b-cells to liver and hepatocytes specifically (4)(5)(6)9,13,(18)(19)(20). TCF7L2 or other transcription factor (TCF) members can interact with b-catenin (b-cat), forming the bipartite transcription factor b-cat/TCF, which serves as the important effector of the Wnt signaling pathway.…”
mentioning
confidence: 99%